Investigation on the Ground Pressure Induced by Hard Roof Fracturing at Different Layers during Extra Thick Coal Seam Mining - Rui Gao; Jingxuan Yang; Tiejun Kuang; Hongjie Liu (Geofluids)
The fracturing of hard roofs in different layers would result in complex ground pressure on the working face, such as supports collapsed and severe roadway deformation. However, the mechanism of the ground pressure induced by hard roof fracturing in different layers is still unclear. In the paper, a physical model of a 20 m extrathick coal seam mined with hard roofs existing was established based on the physical simulation similarity criterion. The overburden fracturing structure, abutment stress distribution, and failure characteristics of the coal body were monitored by a noncontact strain measurement system and resistance strain gauges, to reveal the mechanism of ground pressure induced by hard roof fracturing. Furthermore, on-site measurement was used to monitor and analyze the ground pressure affected by hard roofs in different levels. The results provide a theoretical basis for the control of ground pressure in extrathick coal seam mining with hard roofs.